Pengaruh Penerapan Pembelajaran Berdiferensiasi Menggunakan Model Discovery Learning Terhadap Hasil Belajar Matematika Siswa SD Kelas V UPT SDN 02 Tiumang - Filahanasari, Eka; Putri, Suci Rahma; Parma, Revnita (Universitas Batanghari Jambi, 2024)
This research is based on the learning process that has not shown interesting progress and has not been able to encourage active participation from students. This situation directly has a negative effect on student learning achievement in Mathematics which is still relatively low. Therefore, efforts are needed to develop more effective and interesting learning methods to improve student learning outcomes in these subjects. This study aims to obtain information on how much the Discovery Learning type cooperative learning model has an effect on the learning outcomes of Mathematics students in grade 5 elementary school. This study is an experimental research that uses a pre-experimental research design, with a one-group pretest-posttest design. The location of the research was carried out at SDN 02 Tiumang, Tiumang District, Dharmasraya Regency. The research sample consisted of 22 students who were all 5th grade students. The data collection instrument used is a multiple-choice test of 25 items, which has been tested for validity and reliability. The results showed that the average score of the pretest was 48.18 and the average score of the posttest was 83.64. The description of the data from the analysis of pretest and posttest data, using the Paired Sample T-test showed a significance value of 0.000 < 0.05. From the criteria of the provision, if the significance < 0.05, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence from the application of the Discovery Learning type cooperative learning model on the learning outcomes of Mathematics students in grade 5 of SDN 02 Tiumang.